Anticancer properties of Malaysian herbs: a review - Wan Ghazali, Wan Afiqah Syahirah; Ab Alim, A’attiyyah; Kannan, Thirumulu Ponnuraj; Mohd Ali, Nor Azah; Abdullah, Nurul Asma; Mokhtar@Makhtar, Khairani Idah (The Journal of the School of Dental Sciences, USM, 2016)
Discovery of drugs from medicinal plants continues to provide major leads against various pharmacological targets, particularly in cancer diseases. Hence, there are increasing demands to discover more therapeutic agents from various species of medicinal plants. Chemical compounds in plants are important for human beings due to their therapeutic properties. Goniothalamus umbrosus, Typhonium flagelliforme, Myrmecodia pendens, Strobilanthes crispus and Clinacanthus nutans, are among the herbal species, which are consumed by cancer patients in order to combat against the growth of cancer cells. The present review aims to highlight on the anti-cancer properties of the listed Malaysian herbs.